SOSIALISASI DAN PELATIHAN PEMBUATAN MAKANAN PENCEGAH STUNTING DI DESA TIAMBANG KECAMATAN PEMATANG TIGA KABUPATEN BENGKULU TENGAH - Elwan, Stiadi (UNIB Press, 2024)
Hygiene, environment, and balanced nutrition are some of the factors supporting the growth, development and health of children. Children who do not receive adequate nutrition, a less clean environment and a less family economy can fail to grow and develop. Stunting (small) is a condition of a child's height that is less by age than his peers. Stunting is a condition that is felt by the community so that more knowledge is needed with the community through socialization and training on making stunting prevention food. Tiambang village is a village located in Pematang Tiga District, Central Bengkulu Regency which is one of the regions in Bengkulu province. The implementation of the real work lecture (KKN) as one of the forms of student service of the University of Bengkulu in the real work lecture (KKN) in Tiambang Village provides knowledge and understanding in the form of socialization and training on stunting prevention food as the first step in providing understanding to the community